PEMBAYARAN LETTER OF CREDIT MENGGUNAKAN INTERNET BANKING DALAM TRANSAKSI PERDAGANGAN INTERNASIONAL (STUDI PADA PT BANK PEMBANGUNAN DAERAH JAWA TIMUR, Tbk) - Nugroho, Widhi Cahyo (JHP17 (Jurnal Hasil Penelitian), 2022)
Today Letter of Credit (L / C) is not the only way of payment in import and export activities, but the role of Letterof Credit (L / C) is still important because this way of payment can provide a sense of security, both for the exporter,and for importers ... The formulation of the problem is How is the export-import arrangement by paying Letter ofCredit through internet banking at PT Bank Jatim Tbk? How is the legal protection for PT Bank Jatim Tbk as apayer in Letter of Credit transactions through internet banking. The conclusion is in accordance with the principleof pacta sunt servanda as regulated in Article 1338 paragraph (1) of the Civil Code which states: "all treaties madelegally apply as a law for those who make them" and the principle of good faith stipulated in Article 1338 paragraph(3 ) Civil Code. Internet banking is a real-time online payment service, organized by banks.